Factors Influencing The Finance Information System: Compliance and Supervision, Quality, Utilization of Financial Reports - Ani Santika, Veny (Dinasti Publisher, 2022)
The Literature Review article on Compliance and Supervision, Quality and Utilization of Financial Reports on the Finance Information System is a scientific article that aims to build a research hypothesis on the influence of variables to be used in further research, within the scope of ESSB science. The method of writing this Literature Review article is the library research method, which is sourced from online media such as Google Scholar, Mendeley and other academic online media. The results of this article are that: 1) Compliance and Supervision have an effect on the Finance Information System; 2) Quality influences the Finance Information System; and 3) Utilization of Financial Statements affects the Finance Information System. Apart from these 3 exogenous variables that influence the endogenous variables of the Finance Information System there are many other factors including the variables of Planning, Management, Internal Audit and Controlling.